Active and Play-Based Physical Education Approaches: A Comparative Study in Indonesia and Thailand - Karlina Dwi Jayanti; Abrean Meli Andani; Taraporn Suntorn; Poramet Hema (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aims to compare active and play-based physical education approaches implemented in Indonesia and Thailand in enhancing elementary school students’ motivation, participation, and squat long jump performance. The study also examines differences in instructional strategies, learning environments, and pedagogical characteristics across both educational contexts. Methodology: Methodology: This study employed a comparative classroom action research design with descriptive mixed-methods analysis across two elementary schools: State Elementary School Kentingan 03, Surakarta, Indonesia (n = 28) and Ban Nok Mueang School, Phatthalung, Thailand (n = 30). Data were collected through observations, interviews, questionnaires, and documentation across three phases and analysed using qualitative and quantitative descriptive procedures. Main Findings: Both countries improved instructional quality, student motivation, participation, and squat long jump performance through active and play-based approaches. Indonesian students increased their mean jumping distance by 29.9 cm (+25.3%) through the Active, Innovative, Creative, Effective, and Enjoyable Learning approach, while Thai students improved by 27.7 cm (+22.2%) through structured movement stations and cooperative circuits. These approaches created distinct learning environments that enhanced engagement, confidence, and movement competence. Novelty/Originality of this study: This study provides a comparative analysis of active and play-based squat long jump learning practices between Indonesia and Thailand, which has rarely been explored in previous physical education research. The study highlights the integration of Indonesia’s low-resource instructional creativity and Thailand’s structured movement-based pedagogy as complementary approaches for improving elementary physical education learning quality in Southeast Asian educational contexts.